Dealing with populists in government: the SYRIZA-ANEL coalition in Greece. Issue 2 (18th September 2016) - Aslanidis, Paris; Rovira Kaltwasser, Cristóbal
ABSTRACT: The Great Recession triggered an unprecedented level of political turmoil in Greece, leading to a major readjustment of the party system and the near disappearance of the once mighty socialists of PASOK. Gradually, SYRIZA – a radical-leftist-turned-populist party – rose to become the key electoral player under the aegis of its young and popular leader, Alexis Tsipras. SYRIZA eventually won two general elections in 2015 and ruled together with the populist radical right Independent Greeks (ANEL) as junior partner, a coalition of great analytical significance, representing the first ever governing alliance of left-wing and right-wing populist parties in Europe. This contribution investigates reactions to the SYRIZA-ANEL government, giving special emphasis to measures undertaken by domestic and external actors. A key finding that warrants further research is that, under the same conditions of economic crisis that bring populists to power, economic institutions and material constraints can play an important role in taming populist actors and socializing them into the standard rules of the liberal democratic regime.